Circulating tumor cells and γH2AX as biomarkers for responsiveness to radium-223 in advanced prostate cancer patients - Jonathan Chatzkel; Jesse Mocha; Johnna Smith; Jun-Min Zhou; Youngchul Kim; Ghassan El-Haddad; Jingsong Zhang (Future Science OA, 2020)
Aim: Radium-223 improves overall survival in patients with metastatic castration-resistant prostate cancer to the bone. Radium-223 causes double-strand DNA breaks and produces γH2AX, a potential biomarker for response. We examined the feasibility of tracking γH2AX positivity and numeration in circulating tumor cells. Patients & methods: Ten patients with biopsy-confirmed symptomatic M1b castration-resistant prostate cancer received radium-223 as standard of care and were assessed for γH2AX level changes following doses 1, 3 and 6. Results: Trend tests confirmed that patients with ≥50% increase in circulating tumor cells positive for γH2AX postradium-223 therapy had a lower risk of death (p = 0.035). Conclusion: Regular interval measurements of γH2AX are feasible. The potential correlation between γH2AX changes and overall survival warrants further investigation.